2009
DOI: 10.1002/oti.276
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hemiplegic grasp following distributed repetitive intervention: a case series

Abstract: The purpose of this pilot study was to investigate the efficacy of a distributed model of repetitive and focused intervention on grasp force, and clinical and functional hand measures in persons with chronic hemiplegia and limited hand recovery from self-reported stroke. A case series design was used. Focused repetitive unilateral and bilateral interventions were provided in a distributed manner (three times a week for 6 weeks) to three persons with upper limb hemiplegia of more than 1 year. Data from instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Although physical and occupational therapy dealt with the practice of daily activities, occupational therapy focused on upper extremity functions, such as feeding, dressing and using objects by hand, while physical therapy focused on locomotion, walking, stair climbing, balancing and transfers. Treatment sessions were constructed based on fundamental principles of motor learning, for example, intensive,10 task-specific,9 challenging10 and variable training 11 21. Task-specific, challenging training tasks that are context-dependent were reported to enhance motor performance9 by increasing participation and engagement in practice through motivational salience 22.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although physical and occupational therapy dealt with the practice of daily activities, occupational therapy focused on upper extremity functions, such as feeding, dressing and using objects by hand, while physical therapy focused on locomotion, walking, stair climbing, balancing and transfers. Treatment sessions were constructed based on fundamental principles of motor learning, for example, intensive,10 task-specific,9 challenging10 and variable training 11 21. Task-specific, challenging training tasks that are context-dependent were reported to enhance motor performance9 by increasing participation and engagement in practice through motivational salience 22.…”
Section: Treatmentmentioning
confidence: 99%
“…The nature of the functional recovery demonstrates the importance of adhering to motor learning principles to support the intrinsic neurological recovery, including intensive training,6–8 using task-specific9 and challenging exercises10 within variability of practice 11. A task-oriented treatment (TOT) using these principles was previously reported to be superior to traditional neurodevelopmental approaches12 and to standard physical or occupational therapy delivered with the same intensity and duration 13.…”
Section: Introductionmentioning
confidence: 99%
“…In rehabilitation therapy, repetitive training with FES is best practice [40, 41]. In previous publications, it was observed that size and shape of individually identified VEs remained the same from day to day in the same patient if the electrode array is placed at the same forearm position (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These two papers are framed within the context of occupation-based rehabilitation, and both Hubbard et al and Stoykov and Corcos extend their reviews to include recommendations for the practising clinician. The effect of triweekly intervention for improved grasp function in chronic hemiplegia is examined by Conti and Schepens (2009) in Changes in hemiplegic grasp following distributed repetitive intervention: a case series. Reistetter et al (2009), in Unilateral and bilateral upper extremity weightbearing effect on upper extremity impairment and functional performance after brain injury, provide insight into differences between stroke and traumatic brain injury response to weight-bearing.…”
Section: Occupational Therapy and Neuromotor Interventionsmentioning
confidence: 99%